Freud and the religion - Bertoldo, Fernando Cardoso (Vox Scripturae - Revista Teológica Internacional, 2025)
In this article, we present Freud’s relationship with religion with the purpose of presenting the origin of Jewish and Christian monotheism, as well as developing the genesis of religious phenomena according to Freud from the perspective of obsessional neurosis. This article concludes with the theological possibilities in psychoanalysis through a brief exposition of the dialogue between Freud and Pfister, since this dialogue has changed the history of the dialogue between Psychoanalysis and Religion. Thus, through this exposition, we consider that Freud was restricted to observing religion from the perspective of obsessional neurosis and did not contemplate the possible contributions that psychoanalysis could provide for Christian maturity, although the search for psychical maturity that Freud aimed at with psychoanalysis could contribute to this development according to Pfister
Keywords: Freud; Religion; Obsessive Neurosis; Psychoanalysis and Faith